3r^2=9r

Simple and best practice solution for 3r^2=9r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r^2=9r equation:


Simplifying
3r2 = 9r

Solving
3r2 = 9r

Solving for variable 'r'.

Reorder the terms:
-9r + 3r2 = 9r + -9r

Combine like terms: 9r + -9r = 0
-9r + 3r2 = 0

Factor out the Greatest Common Factor (GCF), '3r'.
3r(-3 + r) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'r' equal to zero and attempt to solve: Simplifying r = 0 Solving r = 0 Move all terms containing r to the left, all other terms to the right. Simplifying r = 0

Subproblem 2

Set the factor '(-3 + r)' equal to zero and attempt to solve: Simplifying -3 + r = 0 Solving -3 + r = 0 Move all terms containing r to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + r = 0 + 3 Combine like terms: -3 + 3 = 0 0 + r = 0 + 3 r = 0 + 3 Combine like terms: 0 + 3 = 3 r = 3 Simplifying r = 3

Solution

r = {0, 3}

You can always share this solution

See similar equations:

| x^2+11x+10=0 | | x^2+2x=0 | | x^2+15x+44=0 | | x^2-64=0 | | r^2-4r-32=0 | | b^2+8b=0 | | n^2+6n+8=0 | | x^2+7x+10=0 | | r^2+7r+12=0 | | m^2-2m-48=0 | | n^2-10n+25=0 | | p^2-7p+12=0 | | k^2+13k+40=0 | | a^2+2a-24=0 | | n^2+15n+56=0 | | v^2+7v-8=0 | | b^2+9b+20=0 | | n^2-11n+24=0 | | x^2-13x+40=0 | | r^2-12r+35=0 | | m^2-5m=0 | | 5x^2=50 | | t^2+7t-35=2t-11 | | 2(x^2)-7x=1 | | x^2+4x-2m=0 | | 27x^2-5x=0 | | 7e^8+t=2 | | 13x^2-28x=0 | | 15n+3n^4-4n+12n^4+n= | | 2x^2-24x=-2x^2-7x-18 | | 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= |

Equations solver categories